Arabic Language Teaching Method Selection Strategy Based on Student Characteristics - Muhammad Zaidaan; N. Lalah Alawiyah (Albariq: Jurnal Pendidikan Bahasa Arab, 2025)
Arabic language teaching in Indonesia faces complex challenges, mainly due to the diversity of learner characteristics that include age, educational background, intelligence level, learning style, and motivation. The selection of teaching methods that do not consider these characteristics often becomes an obstacle in the learning process. This research aims to examine the strategy of selecting effective and adaptive Arabic teaching methods based on learners' characteristics. The research method used is library research with a descriptive qualitative approach. Data were collected through a review of various relevant scientific literature, then critically analyzed to find the relationship between the characteristics of learners and the teaching methods used. The results show that a deep understanding of learners' characteristics is very important in determining the right method, such as direct, communicative, audiolingual, or task-based methods. Method selection strategies that are based on the real needs of students can increase the effectiveness, engagement, and success of Arabic language learning. This research is expected to be a practical reference for teachers in designing a more inclusive and sustainable learning process.